That looks easy! Evidence against the benefits of an easier criterion of success for enhancing motor learning. (May 2023) - Parma, Juliana O.; Bacelar, Mariane F.B.; Cabral, Daniel A.R.; Lohse, Keith R.; Hodges, Nicola J.; Miller, Matthew W.
Abstract: OPTIMAL theory predicts providing learners with a relatively easier criterion of success during practice enhances motor learning through increased self-efficacy, perceptions of competence, and intrinsic motivation. However, mixed results in the literature suggest this enhancement effect may be moderated by the number of successes achieved by learners practicing with the difficult criterion. To investigate this possibility, we manipulated quantity of practice to affect the absolute number of successes achieved by learners practicing with different success criteria. Eighty participants were divided into four groups and performed 50 or 100 trials of a mini-shuffleboard task. Groups practiced with either a large or a small zone of success surrounding the target. Learning was assessed 24 h after acquisition with retention and transfer tests. In terms of endpoint accuracy and precision, there were no learning or practice performance benefits of practicing with an easier criterion of success, regardless of the number of trials. This absence of a criterion of success effect was despite the efficacy of our manipulation in increasing the number of trials stopping within the zone of success, self-efficacy, perceptions of competence, and, for participants with 100 trials, intrinsic motivation. An equivalence test indicated that the effect of criterion of success was small, if existent. Moreover, at the individual level, intrinsic motivation did not predict posttest or acquisition performance. There were no benefits of easing the criterion of success on pressure, effort, accrual of explicit knowledge, or conscious processing. These data challenge key tenets of OPTIMAL theory and question the efficacy of easing criterion of success for motor learning. Highlights: Practice with easier criteria of success had little if any effect on motor learning. Easier criteria of success increased self-efficacy and perceptions of competence. Easier criteria of success enhanced intrinsic motivation in longer length practice. Intrinsic motivation did not predict motor learning at the individual level.